INOVASI PELAYANAN PAJAK MELALUI SMART TAX DI BAPENDA KOTA PEKANBARU - Naada Rizki Syahdilla; Zulkarnaini Zulkarnaini (Cross-border, 2022)
The Smart Tax application is an innovation of local tax services issued by the Pekanbaru City BAPENDA to improve local tax services that make it easier for taxpayers to get the desired local tax services. However, there are obstacles in implementing regional tax service innovations through Smart Tax at the Pekanbaru City BAPENDA, such as the limitations of downloading the Smart Tax application and there are still many taxpayers who do not know this Smart Tax application. This study aims to determine whether the innovation of tax services through Smart Tax at BAPENDA Pekanbaru City has been running well or not. The theory used in this study is the theory of innovation by Rogers in Suwarno with five indicators, namely relative advantage, suitability, complexity, trialability, and ease of observation. This research method uses qualitative methods with data collection techniques based on observations, interviews, and documentation. The results of this study indicate that the innovation of tax services through Smart Tax at BAPENDA Pekanbaru City has not gone well. The factors that hinder the implementation of this program are the server and downloading the Smart Tax application still limited and lack of budget for socialization of Smart Tax application in Pekanbaru City.